Ss-Open sets and Ss-Continuous Functions - Khalaf, Alias B.; H. Majeed, Abdulrahman; M. Jamil, Jamil (International Journal of Advanced Mathematical Sciences, 2014)
In this paper we introduce and study the concept of Ss-open sets .also, a study new class of functions called Ss-continuous functions, the relationships between Ss-continuity and other types of continuity are investigated.Keywords: Ss-open set, Ss-continuous function, semi-open set, semi-continuous functions.